Increased Sensitivity of DMD Lymphoblastoid Cell To Low Doses of X-Irradiation. Issue 2 (1994) - Melchiorri, L.; Carturan, S.; Ferrari, D.; Di Virgilio, F.; Baricordi, O. R.
Abstract : Several cell membrane abnormalities affecting various cell populations have been reported in Duchenne muscular dystrophy (DMD) by different investigators. In peripheral blood lymphocytes intrinsic cellular membrane defect evidentiated by impairment of capping capacities has been repeatedly obtained, suggesting that DMD product could act in such cellular phenotype at the cytoskeletal compartment. It has been previously reported that lymphoid cells are characterized by high radiosensitivity. On the assumption that DMD phenotypes could increase this susceptibility, we have compared the radiosensitivity of normal and DMD lymphoblastoid cell lines (LCLs) to small doses (0-2Gy) of x-irradiation. The results obtained suggest an increased sensitivity of DMD cells without Ca++ uptake or apoptotic phenomena, associated with an effect upon cell cycle length.